Acute and subacute effects of irreversible electroporation on normal common bile ducts in a rabbit model. (15th August 2020) - Li, Qingshan; Ren, Fenggang; Zhang, Yuchi; Chang, Pengkang; Wang, Yue; Ma, Tao; Hu, Liangshuo; Wu, Rongqian; Wang, Bo; Lv, Yi
Abstract: Background/Purpose: This study aimed to evaluate the acute and subacute effects of irreversible electroporation (IRE) on normal common bile ducts (CBDs). Methods: Cell susceptibility to IRE was assessed in vitro with cholangiocarcinoma and normal cell lines. The electric field and temperature distributions were evaluated with a two‐dimensional simulation model of bile duct. In vivo bile duct IRE was performed in 28 adult rabbits. Results: Different cells showed different susceptibility to the effect of IRE, cancer cell line HUCC‐T1 was the least sensitive to IRE. Simulations predicted the distributions of electric field and temperature during the IRE process, and the maximum temperature of tissue was below 43℃. Complications were observed in 8/28 animals (biliary dilatation, n = 4; biliary stricture, n = 4) by postoperative days 7, 14, and 28. Histopathological analyses revealed complete cell death with bile duct wall integrity. Bile duct epithelial recovery was completed between post‐IRE days 14‐28. Conclusions: The normal CBD retains the lumen wall integrity following IRE with immediate periductal placement of the electrode. However, the risk of biliary dilatation and stricture is a reminder that the parameters of IRE need to be determined more precisely to ensure the treatment efficacy and reduce the risk of collateral damage. Abstract : Highlight Li and colleagues evaluated the acute and subacute effects of irreversible electroporation on normal common bile ducts in vitro and in vivo, showing that the common bile ducts retained lumen wall integrity following electroporation. The presence of biliary complications, however, warrants further exploration of the proper parameters of irreversible electroporation.